The effect of urbanization on the intensification of SUHIs: Analysis by LULC on Karachi. (1st October 2020) - Rizvi, Shahnillah Haider; Fatima, Hira; Iqbal, Muhammad Jawed; Alam, Khan
Abstract: This study aims to assess Urban Heat Island (UHI) as Surface Urban Heat Island (SUHI) of Karachi which ensures the existence of UHI effect on sustainability, based on the analysis of rapid urbanization and Land Use Land Cover (LULC) changes on the average temperature warming in Karachi. Satellite images are employed to extract statistics regarding land-use in Karachi city and to obtain land surface temperature (LST) maps for the year 2009 and 2017. LULC map is obtained by applying a supervised classification technique to detect the changes in impervious areas. Maps of daytime surface temperature are retrieved from the thermal band of Landsat images and nighttime LST is extracted from the MODIS. The Urban Heat Island Intensity (UHII) is analyzed to indicate persistent zones. It is found that built-up areas are increased by 40% and the vacant areas are decreased at a huge rate within study period of 8 years, whereas the intensity of UHI is increased by 0.04 °C . The LULC changes play vital role in the variation of surface temperature along with a spatial distribution pattern of UHI. Regression analysis is also carried out to examine the relationship of LST with impervious areas. Highlights: The percentage of built-up areas grew from 25.70% to 36.14% over the study period of 8 years. LULC change is the prevailing factor in LST variation which is closely associated with the materials used in construction. The intensity of UHI has increased by 0.04 °C and the heat island area has also been increased by 1.73 k m 2 in 8 years.